2016
DOI: 10.1093/jnci/djw003
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of Tyrosine Kinase Inhibitor Treatment Strategies for Chronic Myeloid Leukemia in Chronic Phase After Generic Entry of Imatinib in the United States

Abstract: Background:We analyzed the cost-effectiveness of treating incident chronic myeloid leukemia in chronic phase (CML-CP) with generic imatinib when it becomes available in United States in 2016. In the year following generic entry, imatinib’s price is expected to drop 70% to 90%. We hypothesized that initiating treatment with generic imatinib in these patients and then switching to the other tyrosine-kinase inhibitors (TKIs), dasatinib or nilotinib, because of intolerance or lack of effectiveness (“imatinib-first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 49 publications
1
68
1
1
Order By: Relevance
“…The analysis showed an incremental costeffectiveness ratio for the imatinib-first strategy of US$883 730. 26 One important element that should be added to these analyses is the potential for treatment discontinuation. As mentioned above, eligibility for this strategy is augmented by approximately 15% by the initial use of nilotinib compared with imatinib.…”
Section: Cost-effectivenessmentioning
confidence: 99%
“…The analysis showed an incremental costeffectiveness ratio for the imatinib-first strategy of US$883 730. 26 One important element that should be added to these analyses is the potential for treatment discontinuation. As mentioned above, eligibility for this strategy is augmented by approximately 15% by the initial use of nilotinib compared with imatinib.…”
Section: Cost-effectivenessmentioning
confidence: 99%
“…Sacha et al demonstrated non-inferiority of generic imatinib in clinical efficacy and tolerability compared to branded imatinib in Poland at a significantly lower cost [30]. Padula et al [6] used Markov models to compare the 5-year cost-effectiveness of an 'imatinib first' (i.e. step-edit) versus 'physician's choice' that allowed for the initiation of any one of the three TKIs approved for first-line use, in achieving complete cytogenetic response (CCyR) and early molecular response (EMR).…”
Section: Generic Imatinib Step Editmentioning
confidence: 99%
“…First, the model allowed only one opportunity to switch within the first 12 months after treatment initiation during a 5-year time horizon [6]. NCCN guidelines recommend regular evaluations of the response to treatment every 3-6 months depending on time on therapy.…”
Section: Generic Imatinib Step Editmentioning
confidence: 99%
See 1 more Smart Citation
“…Anticipating the introduction of generic imatinib into the USA, Padula and colleagues 3 conducted an analysis to estimate the cost-effectiveness of chronic phase CML therapy over a 5-year timeframe (2016–2021). The investigators compared upfront generic imatinib with ‘physician choice’ of frontline treatment using one of three TKIs, selected randomly: dasatinib (Sprycel), nilotinib (Tasigna), or patented imatinib (Gleevec) 3 .…”
mentioning
confidence: 99%